Needs Analysis Utilization of Fuzzy Delphi Method in Catholic Children's Faith Formation Curriculum Development in St. Peter Parish Palembang - Ermayanti, Ermayanti; Prasetyo, Recardus Eko; Yosef, Yosef (Journal of Educational Sciences, 2025)
This research is motivated by the importance of developing a Catholic Child Faith Development curriculum that is relevant to the needs of child development in the digital era and a pluralistic society, especially in St. Peter Parish Palembang. This research aims to analyze the needs of curriculum development with the Fuzzy Delphi Method (FDM) approach. The aspects measured include: the relevance of teaching materials, the effectiveness of learning methods, the availability of meaningful learning media, and the level of stakeholder participation in curriculum planning. The method used was a mixed qualitative and quantitative approach through the FDM technique, involving a panel of experts consisting of pastors, children's faith companions, parents, and church leaders. The results showed that most of the indicators had not reached the optimal level of consensus, especially in the aspects of learning methods and media that were considered less interactive and not contextualized with the development of today's children. Stakeholder participation is also still limited. In conclusion, the development of an FDM-based curriculum is a strategic step to produce a curriculum that is more innovative, contextual, and collaborative, and is able to answer the challenges of children's faith development in a more inclusive and targeted manner.